Trends in food and nutrition behaviours, knowledge, and attitudes among youth in six countries: findings from the 2019-2021 International Food Policy Study Youth Surveys - Rachel B. Acton; Christine M. White; Karen Hock; Lana Vanderlee; David Hammond
Abstract Objective: This commentary highlights the release of findings now available in the report International Food Policy Study Youth Surveys: Summary of Findings 2019-2021. Design: The survey data described in this commentary consist of repeated cross-sectional surveys conducted annually beginning in 2019. Setting: Online surveys were conducted in 2019 to 2021 among respondents living in Australia, Canada, Chile, Mexico, the United Kingdom and the United States. Participants: Survey respondents were youth aged 10 to 17 years in 2019 (n=12,031), 2020 (n=11,108) and 2021 (n=10,459). Results: The report described in this commentary summarizes findings on food and nutrition behaviours, attitudes, and knowledge among youth, including their diet sources and patterns, school nutrition environments, food security, diet intentions, weight perceptions and weight loss behaviours, sugary drink perceptions, awareness of public education and mass media campaigns, perceptions of food labels, and exposure to food and beverage marketing. Conclusion: Results from the IFPS Youth surveys provide important insights into key policies of global interest, including front-of-package nutrition labelling, levies on sugary beverages, and restrictions on marketing unhealthy food and beverages to children. As policymakers continue to seek effective strategies to improve adolescent health outcomes, ongoing cross-country monitoring of food and nutrition-related indicators, such as the data from the International Food Policy Study, will be critical in assessing dietary trends and evaluating upcoming policies.